An Ethnographic Study of the Diversity of Indonesian Coffee Processing and Preparation - Purnomo (Journal of Coffee and Sustainability, 2025)
Indonesia is one of the world’s largest coffee-producing countries. Each region produces coffee with distinctive characteristics that serve as a form of regional branding based on its area of origin. In addition, Indonesia possesses a wide variety of unique coffee processing and serving traditions that reflect local cultural characteristics and the surrounding natural resources. The aim of this study is to analyze the diversity of traditional coffee preparations, the types of additional ingredients used, serving techniques, and the historical value of coffee in Indonesia. This research employs a qualitative approach using a literature study method. Data were collected through a comprehensive review of academic journals, books, official reports, and credible online sources related to traditional Indonesian coffee, gastronomy, and cultural heritage. The collected literature was analyzed descriptively to identify patterns of diversity in preparation methods, ingredients, serving techniques, and the socio-cultural values attached to coffee traditions in various regions. The findings indicate that Indonesia has a wide range of traditional coffee preparations distributed across different regions. Each preparation and serving style is influenced by factors such as the availability of raw materials, community traditions, geographical conditions, and the social functions of coffee within society. Aceh Province is identified as the region with the greatest diversity of traditional coffee preparations. Traditional coffee products in Indonesia have significant potential to be recognized as intangible cultural heritage, to strengthen the gastronomic identity of the archipelago, and to support regional branding and coffee-based ecotourism.